Tecnologias, mídias, criação e hipertextualidade na transformação da informação em conhecimento interativo - Jorente, Maria José Vicentini [UNESP] (2009)
The object of study of this research is defined in terms of cognitive and emotional changes in the process of acquiring knowledge, supported by new technologies of information and communication (ICTs): how these changes transform the old paradigms of Information Science. The hypothesis is that the generation of products of contemporary creation is influenced and facilitated by new forms of perception and sensitivity offered by postvanguard media. The thesis is that procedures used to prepare professional designers in imagery can be extended, as far as the media invade the cognitive process of knowledge nowadays, determining means of perception, procedures and facilitating access to information as a whole. The technology interfaces interfere in shaping information and its perception, dissemination and reproduction in hypertextual and intersemiotical’s systematic interactions. The proposed update of the concepts and procedures is based on the actualization of the concepts of science and contemporary art treated in accordance with new paradigms of Information Science. In these, science and aesthetics go together in order to create environments of communication conveyed by self-organization and new habits of selfarchiving. They are controlled by peers and mentors in daily pages, terms of annotation of electronic communication, leading to empowerment through collaborative practice. The thesis articulates a theoretical universe with application in laboratory practices. The theoretical basis is defined within the environment of the object of study -the information conveyed by the media as a post-vanguard dynamic chaotic subsystem permeated by other subsystems- such as semiotics, especially intersemiotics translations and hybridizations modeled by the media in post-vanguard. Concepts of remix and reproducibility are treated subsequently to the intersemiosis. It is also sought to identify... (Complete abstract click electronic access below)